TANGGUNG JAWAB HUKUM RUMAH SAKIT DI ERA DIGITALISASI PELAYANAN KESEHATAN - Widjaja, Gunawan; Ersita Yustanti, Dyah (Penerbit Lafadz Jaya, 2025)
The digitisation of healthcare services has brought significant changes to hospital management, particularly in relation to data protection and legal responsibility for electronic medical records. This study aims to analyse the forms of legal responsibility of hospitals in the era of healthcare digitisation based on applicable regulations in Indonesia. The method used is normative legal analysis with a legislative approach and analysis of primary and secondary legal literature. The findings indicate that hospitals have multidimensional legal responsibilities, encompassing civil, criminal, and administrative aspects, in ensuring the security, confidentiality, and integrity of patient data. The implementation of electronic medical records requires hospitals to adopt data protection standards, information security systems, and mechanisms for reporting and regular audits in accordance with Ministry of Health Regulation No. 24 of 2022, Law No. 27 of 2022 on Personal Data Protection, and Law No. 44 of 2009 on Hospitals. Negligence in managing digital data can result in legal sanctions and losses for patients. Therefore, hospitals are required to improve their technology management, human resource capacity, and compliance with regulations to ensure the protection of patient rights in the era of digitalisation of healthcare services.